Mineralogy Characteristic Study and Exploration on the Valuable Metals Enrichment of Coal Fly Ash. (27th October 2019) - Chen, Tao; Yan, Bo; Li, Li-li; Yan, Zi-Ang; Wang, Jun; Xiao, Xian-ming
Abstract : The separation and enrichment can be targeted to enrich in fly ash and reduce the cost of leaching and recovering of fly ash. Regarding their different properties, the single-component separation was used to obtain uncompleted burned carbon, glass microbeads, minerals, and other characteristic components from the ash. Also, the mineral composition of each component was analyzed by electron microscopy. The metal minerals were mainly concentrated in the mineral components. Besides, the electron probe microanalysis shows that the Pt content in the minerals of fly ash was significantly correlated with the metal contents of Ni and Cu. After the obtainment of the characteristics of fly ash metal enrichment, the heavy minerals with Cu, Ni, Pt, Pd, and other target metal elements were enriched by gravity separation and flotation. The enrichment coefficients of Cu, Ni, Pt, and Pd were 1.45, 1.33, 1.90, and 1.60, respectively, and the recovery rates were 77%, 81%, 97%, and 88%, respectively. Since the yield of heavy minerals obtained by separation was 62.24%, it indicated the physical separation method could significantly reduce the cost of leaching and recovering of fly ash metal resources.